TIMOR LESTE’S ACCESSION TO ASEAN 2011: AN ANALYSIS OF INTERNATIONAL FACTORS - Puguh Toko Arisanto (Universitas Jenderal Ahmad Yani, 2020)
Abstract: After gaining its independence in 2002, Timor Leste struggled for joining ASEAN’s membership. Timor Leste changed foreign policy orientation from PIF to ASEAN. Then, Timor Leste had put its decision in 2011 which officially enrolled as member of ASEAN. This article seeks to analyze Timor Leste’s decision to join ASEAN’s membership. The authors sought to find the answers by using foreign policy decision-making model. This article focused on international factors which are derived from two important variables namely international context and economic and military conditions. The authors found from international context that Timor Leste decided to join ASEAN due to ASEAN’s attractiveness as prospective regional organization and strong support emanating from Indonesia as an influential state regionally. Economic conditions comprise close economic relations of Timor Leste with ASEAN countries. Military conditions are analyzed from Timor Leste’s military capability amidst neighbor’s military capability and its need to collective security. Keywords: Foreign Policy, Decision-Making Model, International Context, Economic and Military Conditions